Regular Physical Activity Helps Improve the Physical Fitness Level of Elementary School Students During the COVID-19 Pandemic - Ilmul Ma'arif; Risfandi Setyawan; Mohammad Zaim Zen; Kahan Tony Hendrawan; Joan Rhobi Andrianto (OVS LLC, 2023)
The purpose of this study was to prove the effect of regular physical activity in helping to increase the physical fitness level of elementary school students during the coronavirus disease 2019 (COVID-19) pandemic. Materials and methods. This research is true experimental with the randomized pretest-posttest control group design. A total of 48 students from the Kabuh District Public Elementary School, Jombang Regency, East Java, Indonesia, aged 10-11 years participated in the study. The students were divided into two groups, namely the control group (G1; n = 21) and the experimental group (G2; n = 27). Measurement of physical fitness level using a) body mass index (BMI); (b) sit-and-reach test; (c) lie down for 30 seconds; (d) pull-up modification; and (e) the 20-meter multistage shuttle run test was performed before and after treatment. The data analysis technique used the Statistical Package for Social Sciences (SPSS) software version 21. Results. The results showed that there was a significant difference in the average level of physical fitness between the pretest and posttest in the experimental group (G2) (p ≤ 0.001), while the control group (G1) did not show a significant difference (p ≥ 0.05). Conclusions. Based on the results of the study it was concluded that providing regular physical activity had a positive impact on increasing the level of physical fitness in elementary school students during the COVID-19 pandemic.